Perjanjian Alih Teknologi Melalui Usaha Patungan Antara â€Enterpriseâ€ dengan Perusahaan Perintis (Lex Jurnalica, 2011)
Natural resources in oceanic seabed has been declared in International Maritime Law Convention as heritage for all people, which it exploration, exploitation, production, and distribution, required science and technology. This thing constituted by reality that limited science and technology mastered by several advanced industrial states, while natural resources, geographically not spread over widely in the world, most often the biggest natural resources spread in several developing countries.To avoid domination monopolies the source of natural resources by developed countries (industrial states) with their science, technological and capital, required the compensation for exploitation and exploration with 1 (one) term and condition which is the existence of transfer of technology with hope can be distributed fairly among developing countries. Through International Maritime Law Convention, arranged rights and obligations of developed countries (industrial states) to transfer of their techno-logy to developing countries as receiver.Indonesia as member of International Maritime Law Con-vention has adopted the convention into national legislation. Transfer of technology aspects between Investor that mastering science and technological with Join Company to be certain company, intentio-nally formed for the agenda to explored and exploited the natural resources and implication must be evaluated from national importance for the agenda of wealthy people.Keywords: Transformation, Technology, Agreement